Antara Cinta dan Obsesi: Representasi Id dalam Perilaku Tokoh Mardio pada Cerpen Karya Eka Kurniawan - Azizah, Fauziyah; Saputra, Kaman Jaya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the personality of the main character in a short story “Cinta Tak Ada Mati” by Eka Kurniawan. The main character, named Mardio, was chosen as the object of research because his personality is related to sexual fantasy, libido, aggression, repression, and obsession which clearly reflect id personality traits. This research uses a qualitative research method with the technique of simak catat. The theoretical study used is Sigmund Freud's “id” personality theory. The main data comes from the short story “Cinta Tak Ada Mati” by Eka Kurniawan. The results show five main manifestations of Id in this character, namely in the form of intense sexual fantasies towards women, libido urges manifested in speech and physical actions, aggression as a form of transformation of inhibited desires, repression of sexual desires for sixty years, and pathological obsessions that reach necrophilic levels.